2013
DOI: 10.1177/159101991301900310
|View full text |Cite
|
Sign up to set email alerts
|

Brain Reorganization after Endovascular Treatment in a Patient with a Large Arteriovenous Malformation: The Role of Diagnostic and Functional Neuroimaging Techniques

Abstract: We describe a case of brain cortical reorganization after embolization of a large right temporal arteriovenous malformation. A comprehensive imaging protocol, including functional magnetic resonance imaging (fMRI), cortical thickness analysis and 320-row computed tomography (CT) perfusion was used to provide information on brain plasticity and potential steal phenomenon. A 25-year-old man known for a right temporal grade V Spetzler-Martin classification arteriovenous malformation (AV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
3
1
Order By: Relevance
“…There are numerous reports of a steal syndrome leading to motor deficits similar to those seen in our patient. 13,[22][23][24][25][26] However, directly conflicting with our patient's presentation, other reports have documented decreased sensation or even numbness to the body. 16 But this is not the first instance in which neurological pathologies result in opposing pain responses.…”
Section: Observationscontrasting
confidence: 86%
“…There are numerous reports of a steal syndrome leading to motor deficits similar to those seen in our patient. 13,[22][23][24][25][26] However, directly conflicting with our patient's presentation, other reports have documented decreased sensation or even numbness to the body. 16 But this is not the first instance in which neurological pathologies result in opposing pain responses.…”
Section: Observationscontrasting
confidence: 86%
“…The interventional therapy group still contains patients awaiting initiation or completion of treatment at the discretion of the local investigator team. Later outcome status might show whether those whose modified Rankin score is 2 or higher will undergo brain functional reorganisation cited in some brain arteriovenous malformations 29 to the degrees known in focal brain infarcts. 30 The range of potential outcome events and potential changes in the clinical status gathered over the coming 5 years should provide important clinical insights into the best long-term management of patients diagnosed with an unruptured brain arteriovenous malformation.…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al 13 reported a case of a patient with a right temporal AVM who showed improvement in IQ and visual memory after AVM excision. La Piana et al 18 reported a case of patients harboring right temporal S-M grade V AVM, presenting with progressive hemiparesis, who showed improvement in their neurologic status after partial embolization and motor cortex reorganization, which was documented on computed tomography perfusion scans. The fact that especially highgrade lesions scored lower in their composite score implies that a steal phenomenon caused by the AVM is in fact a wholebrain problem.…”
Section: Discussionmentioning
confidence: 99%